2015
DOI: 10.1038/nrmicro3448
|View full text |Cite
|
Sign up to set email alerts
|

Recent functional insights into the role of (p)ppGpp in bacterial physiology

Abstract: The alarmone (p)ppGpp is involved in regulating growth and several different stress responses in bacteria. In recent years, substantial progress has been made in our understanding of the molecular mechanisms of (p)ppGpp metabolism and (p)ppGpp-mediated regulation. In this Review, we summarize these recent insights, with a focus on the molecular mechanisms governing the activity of the RelA/SpoT Homologue (RSH) proteins, which are key players that regulate the cellular leves of (p)ppGpp, the structural basis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
773
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 711 publications
(799 citation statements)
references
References 130 publications
(206 reference statements)
12
773
0
14
Order By: Relevance
“…Specifically, transcriptomic and proteomic analysis demonstrated that E. faecalis strongly induces several high-affinity Fe, Mn, and Zn transporters in blood and urine, suggesting that acquisition of these trace elements is important for growth and persistence of E. faecalis in the host environment (19)(20)(21). To test if the growth and survival defects of the E. faecalis Δrel ΔrelQ [(p)ppGpp 0 ] strain in blood (or serum) are due to metal starvation, growth and survival of the parent (OG1RF) and (p)ppGpp 0 strains were monitored in plain horse serum (HS) or HS supplemented with 1 mM FeSO 4 , 1 mM MnSO 4 , or 1 mM ZnSO 4 . Zn is a transition metal essential for protein structure and function that is also withheld from pathogens during systemic infections and was therefore included in our panel of metal cofactors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, transcriptomic and proteomic analysis demonstrated that E. faecalis strongly induces several high-affinity Fe, Mn, and Zn transporters in blood and urine, suggesting that acquisition of these trace elements is important for growth and persistence of E. faecalis in the host environment (19)(20)(21). To test if the growth and survival defects of the E. faecalis Δrel ΔrelQ [(p)ppGpp 0 ] strain in blood (or serum) are due to metal starvation, growth and survival of the parent (OG1RF) and (p)ppGpp 0 strains were monitored in plain horse serum (HS) or HS supplemented with 1 mM FeSO 4 , 1 mM MnSO 4 , or 1 mM ZnSO 4 . Zn is a transition metal essential for protein structure and function that is also withheld from pathogens during systemic infections and was therefore included in our panel of metal cofactors.…”
Section: Resultsmentioning
confidence: 99%
“…We also determined that the Zn concentration in all medium preparations was ϳ70 ng ml Ϫ1 . Considering that Zn is not a component of the FMC recipe, these small amounts of Zn were likely due to trace element contamination 4 . Aliquots taken at selected time points were serially diluted and plated on TSA plates for CFU enumeration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The specific nature of the starvation (i.e., the type of nutrient that has become limiting for growth) and the time spent under nutrient limiting conditions affect the accumulation of these modulators of transcription, presumably allowing cells to target their stress response to best compensate for the shortage of particular metabolites. 58,67-70 Similarly, we reckon that tRNA degradation may only be beneficial during exposure to a subset of the possible stressors a bacterium may encounter. In our study 14 (as in most other studies on the stringent response, reviewed in refs.…”
Section: Why Degrade Trna?mentioning
confidence: 99%